Progesterona estrógenos y expresión de integrinas en la gestación temprana porcina (Veterinary Science, 2017)
Progesterone, estrogen and integrins expression in porcine early pregnancy Porcine placenta is epitheliochorial, adecidua, folded, non-invasive and diffuse. Due to its location as a barrier between mother and embryos, mit becomes both the natural target of the endocrine system and the expression of adhesion molecules and their ligands such as integrins.The aim of this study was to correlate placental expression of αvβ3,β1,β3 y β3 integrins with progesterone and estrogen concentrations present in serum and placental extracts during porcine early pregnancy. 25 mixed breed pregnant sows assembled in three periods: 5 d, 15-20 d and 23-49 d and 6 non-pregnant were used.The presence of integrins by direct and indirect immunoperoxidase was fixed Determination of progesterone (P4) and estrogens (E2) by chemiluminescent immunoassay in solid phase was fulfilled.The expression of all the studied integrins was greater in the period of post-implantation (23-49 d of gestation), followed by the period of pre-implantation (5 d of gestation). The concentrations of serum P4 (ng/ml) in empty sows were lower to those of the pregnant swines (12.53+-7.53 vs. 43.77+-6.92,P0.01).The concentrations of P4 in maternal placental extracts (HoPM) were similar in empty and pregnant swines (P0.35) and among the different periods of gestation studied (P0.13). Serum E2 concentration (pg/ml) in empty sows were similar to those of pregnant swines (19.36+-4.83 vs. 23.15+-4.40, P0.49).While in HoPF were higher to those of HoPM (3864.26+-501.43 vs. 895.42+-515.17, P0.01). In conclusion, it is postulated that the expression of the integrins studied in the uterus during porcine early pregnancy accompanies the presence of E2, secreted mainly by the fetal placental
Keywords: Integrins; Progesterone; Estrogens